Pengaruh Penerapan Metode Logical Consequences Terhadap Kepatuhan Anak Usia Dini Pada Aturan Sekolah Di PAUD Daruth Tholibin - Wardani, Elia; Apriliani, Melani (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2022)
The purpose of this study is to reveal how the influence of early childhood compliance with school rules through the Logical Consequences Method in Daruth Tholibin's early childhood. The research design used in this classroom action research is the Kemmis and Mc Taggart model, the cycle in this model includes developing an action research design known as planning, implementing action, observing, and reflecting. This study uses 3 cycles with 12 meetings. The subjects of this study were students in groups A and B, totaling 20 students at PAUD Daruth Tholibin. Observational data collection techniques, and documentation, how to analyze data using data reduction, data exposure, conclusion drawing and verification. The results of this study indicate that the application of the Logical consequences method can increase compliance for early childhood, especially in Daruth Tholibin Early Childhood Education. With the results of BM 0%, M 40% AND 60% SM.